Politological View on the Free of Primary Education in the DRC (Global Journal of Human-Social Science, 2024)
As most of the developing countries in Sub-Saharan Africa the Democratic Republic of the Congo is known as singular about the delay in the field of education on the one hand and the free primary education on the other hand whence the levels of education and training of its people are getting retrogressed day by day The daily voices to decry not only the steep drop in the level of education but also the cost of quality and effective teaching which falls over the heads of the parents in schools with the consequence that we are seeing the rise of illiteracy compared with the rate of population increase For this purpose it is not enough that the constitutional and legal provisions are of the free primary education a shot principle of international and regional legal instruments we need to clear the State of affairs and the relationship between these provisions and the effectiveness of this free issue itself of the right to education The notion certainly concern to the State public authorities private actors companies and civilians NGO nongovernmental organizations but between them the issue related to its implementation some State public authorities prefer to leave it obsolete letter or at least to find a formula that can be a great burden on them so that others private and civilian actors claim the immediate effective and absolute principle application
Keywords: promoting free; primary education; education for all; teacher; parents; government